What Makes Leadership Training Work? – A Process Evaluation - Pousette, Anders; Grill, Martin (Scandinavian journal of work and organizational psychology, 2025)
This study investigated how contextual circumstances, managers' mental models, and intervention design and implementation facilitated or hindered the development of leadership performance during leadership training. Managers (n = 59) in local government municipalities participated in managerial behaviour training over a period of three months. Leadership performance was assessed by subordinates of these managers before (n = 406) and after (n = 377) the training period. The participating managers reported on contextual circumstances and their mental models before the training started. Data on implementation was collected from the participating managers and the trainers at the end of each of the six training sessions. Transfer of leadership training was facilitated by managers' support from their superior management and managerial colleagues and hindered by taxing job demands in terms of role stressors. The participating managers' readiness for change improved the transfer of the training. Participants' and trainers' assessments of intervention activities showed that the training worked very well throughout; that is, the average ratings of the intervention activities were very high. Thus, there was no opportunity to detect any impact on the transfer of specific intervention activities. This study shows the importance of managers' working conditions in providing managers with good opportunities to develop as leaders. Keywords: Leadership training, transfer, context, process evaluation